Floating Schools: an Overview of Education in Bangladesh - M. Tariq Ahsan (Journal of Education and Teacher Training Innovation, 2023)
highlighting education in Bangladesh is currently attracting world attention because there is a unique phenomenon that occurs due to the process of learning activities on boats in Bangladesh. Teaching and learning activities on a boat are not done because we want to exist and deliberately steal the world's attention because conditions must force these activities to occur. Bangladesh is a country that is prone to flooding problems which can paralyze life activities including educational activities. Problems arise from many parties who question the safety of teachers and students there because learning activities are not carried out in patented buildings. Then many parties also want to know the obstacles that arise from learning activities held on boats. The aim of this research is to determine safety efforts and also the obstacles faced during the learning process. This research uses mixed research methods, namely field research and literature study. The sources for this research are the manager of learning activities on the boat, 5 teachers and 10 students from 3 schools and also several relevant previous articles which were used as reference sources. The results of this research show that there is a guarantee of safety from the management, including starting from boat design , time management, provision for teachers to master the terrain and equipping the boat with sophisticated equipment. The challenges faced include aspects of funding, climate change, limited reach, teacher training and technological infrastructure.